Literatur Review: Peran Masjid Sebagai Pusat Rehabilitasi Mental Spiritual - Revitalisasi Fungsi Sosial Keagamaan di Era Modern - Hasanah, Ummatul; Dewi, Erlitha Azhari; Nurhadji, Nurhadji; Maududi, Abul A'la Al (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Mental health problems continue to rise globally, and Indonesia still faces high prevalence rates, stigma, and limited access to mental health services. In Islam, the mosque holds significant social and spiritual functions that can be strengthened as a community-based rehabilitation center. This review examines Islamic perspectives on mental well-being and explores opportunities to integrate them with modern public health approaches. Findings indicate that revitalizing the mosque’s social role through spiritual practices, counseling, education, and congregation-based support can enhance mental health promotion and prevention efforts. Integrating Islamic spiritual values with psychosocial strategies offers a more holistic and culturally relevant model of mental health care for Muslim communities.